Fiduciary Duties, Conflict of Interest, and Proper Exercise of Judgment - Valsan, Remus (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
One of the foremost problems of fiduciary law theory is the imprecise understanding of what a situation of conflict of interest involves. The mainstream contemporary legal literature on fiduciary duties is premised on the dual assumption that, on the one hand, humans are inclined to act self-interestedly and, on the other hand, they are too weak to consciously resist this urge while managing another person’s interests. Although these assumptions may be true in many cases of breach of fiduciary duties, they do not suffice to explain why fiduciary duties are imposed in situations where a fiduciary’s good faith and honesty cannot be questioned. This article proposes a novel understanding of the notion of conflict of interest. Building on insights from cognitive psychology, behavioural economics, and philosophy, this article defines a conflict of interest as the situation where a person, who has a duty to exercise judgment for the benefit of another, has an interest that tends to interfere with the proper exercise of his or her discretion. The emerging interdisciplinary theory of conflicts of interest shows that personal or extraneous interests interfere with a decision maker’s judgment in unpredictable ways, despite the decision maker’s honest efforts to keep them aside. This theory offers a more persuasive rationale for the strictness of fiduciary liability. It also offers a potent argument against the recent calls to relax the strict fiduciary regime in commercial contexts.